« Les Acta apostolorum apocrypha dans le corpus littéraire vieil-anglais: Acta Andreae » - Faerber, Robert (Apocrypha, 2005)
Abstract The apocryphal acts of the apostles are to be found in a vernacular language, Old-English, for the first time in England, either as translations for monastic reading, or as homilies for the feasts of the apostles, or in poetic forms. It is the Acts of Andrew that have found a privileged position in the literary Old-English corpus in these various forms. The present article is a translation with commentary first of the legend of Andrew among the anthropophagi, then of Andrew's passion, according to the Epistle of the deacons and priests of Achaia, used in a homily for the feast of Andrew. Abstract C'est en Angleterre que nous trouvons les Actes apocryphes des Apôtres pour la première fois en langue vernaculaire, le vieil-anglais, sous diverses formes: traduction et/ou adaptation de textes latins pour la lecture monastique, utilisation de l'apocryphe dans l'homélie pour la fête de l'apôtre, mais aussi sous forme poétique. Ce sont les Actes d'André qui sont ainsi attestés dans le corpus littéraire vieil-anglais. Le présent article propose la traduction avec commentaire d'une part de la légende d'André chez les anthropophages et, d'autre part, de la passion d'André, selon l'Épître des presbytres et diacres d'Achaïe, utilisée dans une homélie pour la fête de l'apôtre.